2018
DOI: 10.1002/prep.201800059
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Long Chain Bonding Agent of CSRP and its Effect on Propellant Mechanical Properties

Abstract: Mechanical properties of composite solid rocket propellant are one of the most important propellant specifications and also improvement of the interfacial interactions between bonding agents and solid particles is a demand for composite solid propellants in order to withstand stresses produced due to various loading conditions, changes in environmental condition, transportation and handling. In this work, long chain bonding agent prepared from the reaction of fatty monocarboxylic acid and dicarboxylic acid wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Bonding agents for composite propellants containing AP as oxidizer are investigated in depth by various research groups. However, for nitramine based energetic fillers such as HMX (cyclotetramethylene tetranitramine) and RDX (cyclotrimethylene trinitramine) very limited bonding agents are explored . Allen has reported that animal‐derived water‐soluble collagen protein for encapsulating the nitramine oxidizers.…”
Section: Bonding Agents For Nitramines Based Composite Propellantmentioning
confidence: 99%
See 2 more Smart Citations
“…Bonding agents for composite propellants containing AP as oxidizer are investigated in depth by various research groups. However, for nitramine based energetic fillers such as HMX (cyclotetramethylene tetranitramine) and RDX (cyclotrimethylene trinitramine) very limited bonding agents are explored . Allen has reported that animal‐derived water‐soluble collagen protein for encapsulating the nitramine oxidizers.…”
Section: Bonding Agents For Nitramines Based Composite Propellantmentioning
confidence: 99%
“…The dewetting problem can be reduced by coating the solid particle surface with coupling agents which forms physical bonds with the binder matrix. In recent times, various bonding agents are being used in the field of composite propellant . This review focuses on the development of bonding agents employed in composite propellants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, scholars have conducted various studies on the interface interaction of explosive composite particles [8–12] . One of the common methods is adding a bonding agent to composite particles, which can improve the coating effect of the binder on the explosive crystals and enhance the mechanical properties [13–17] . Zhang et al [18,19] .…”
Section: Instructionmentioning
confidence: 99%
“…In the development of solid rocket motors, the mechanical properties of solid propellants have become more challenging to achieve [1]. With the increase in the ratio of length to diameter for long‐range rockets, the flexible deformation of the missile body and its effects on ballistic performance have attracted more attention [2].…”
Section: Introductionmentioning
confidence: 99%